An observation of SME foundation promoting capital market to SMEs in Bangladesh as an alternative source of financing through Qualified Investor Offer (QIO) - Saadman, Rafa (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.